The Financialization of the Property Sector: the Case of the Swiss Pension Trusts (1994-2005) - Thierry Theurillat; Jose Corpataux; Olivier Crevoisier (European Regional Science Association (ERSA), 2006)
About 15% of the fortune of the Swiss pension funds has been invested in real estate from 1994 to 2002. Pension trusts have two possibilities in their investment policy, either owning and being responsible for the buildings directly or buying shares in investment vehicules whose localization is mainly in Zurich. In the first case, pension trusts behave as contractors and investors at the same time, which requires staff and moreover knowledge of the real estate markets. Investments which are done at a regional scope and concern chiefly rental apartment buildings are evaluated inside the pension trusts. In the second case, pension trusts are only investors and investments are evaluated through market criterias such as yield, risk/ diversification and liquidity. Basically only the main urban regions of the country are considered for real estate investments that also concern chiefly rental apartment buildings in this case. The change of territorial scale doesn't seem to reduce the risk of real estate investments and the question of the expected yield can be of relevant.
Keywords: 330